Teaching Materials for Fairy Tales Based on Traditional Games for Indonesian Children in Character Development in Elementary - Rismawati, Fitriyani; Kusmana, Suherli; Wilsa, Jaja (PT Inovasi Pratama Internasional, 2025)
This research aims to identify and meet the needs of teaching materials, especially fairy tale text materials based on traditional Indonesian children's games in the form of accompanying textbooks and their implementation, so that they can develop character, especially for Pancasila students in elementary/MI students. The method used in this research was research and development, and the model used was the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) model. The results obtained show that teaching materials for fairy tales based on traditional Indonesian children's games in character development in elementary schools are suitable for use as teaching materials. The learning resources are several fairy tale texts in the form of folk tales combined with traditional games from various regions on the island of Java, which are analyzed, meet the requirements structurally and linguistically, and have character value as teaching materials developed in the form of textbook teaching materials. The development of teaching materials for fairy tales is adjusted to indicators of competency achievement and learning outcomes that are validated by experts to obtain a category of teaching materials that are suitable for use in Elementary Indramayu Regency. Based on the results of testing teaching materials in learning, it is known that these teaching materials are effective in developing the characteristics of elementary students